Treatment of the Supernatant of Anaerobically Digested Organic Fraction of Municipal Solid Waste in a Demo-Scale Mesophilic External Anaerobic Membrane Bioreactor - Giménez-Lorang, Antonio; Vázquez-Padín, José Ramón; Dorado-Barragán, Cecilia; Sánchez-Santos, Gloria; Vila-Armadas, Sandra; Flotats-Ripoll, Xavier (Frontiers in Bioengineering and Biotechnology, 2021)
In this study the supernatant obtained after the anaerobic digestion of OFMSW was treated in a mesophilic demo-scale anaerobic membrane reactor (AnMBR) at cross flow velocities (CFV) between 1 and 3.5 m·s-1. The aim was to determine the process performance of the system. In previous anaerobic CSTR tests, without ultrafiltration, specific gas production between 40 and 83 NL CH4·kg-1 COD fed and removals in the range 10 % - 20 % total COD or 59 % - 77 % soluble COD were obtained, for organic loading rates (OLR) between 1.7 and 4.4 kg COD·m-3 reactor d-1. Data helped to identify a simplified model with the aim of understanding and expressing the process performance. In AnMBR configuration, COD removal has been in the ranges 15.6 – 38.5 % and 61.3 – 70.4% for total and soluble COD, respectively, with a positive correlation between solids retention time (SRT, between 7.3 and 24.3 days) and total COD removal. The constant used in the model expressing inhibition, attributable to the high nitrogen content (3.6±1.0 g N-NH4+·L-1), indicated that this inhibition decreased when SRT increased, explaining values measured for volatile fatty acids concentration, which decreased when SRT increased and the OLR decreased. The alkalinity was high enough to allow a stable process throughout the experiments. Constant CFV operation resulted in excessive fouling and sudden trans-membrane pressure (TMP) increases. An ultrafiltration regime based on alternation of CFV (20 minutes with a certain CFVi and then 5 minutes at CFVi +1 m·s-1) allowed the membranes to filter at a flux (standardized at 20ºC temperature) ranging from 2.8 – 7.3 L·m-2·h-1, over 331 days of operation, even at very high suspended solids concentrations (>30 g Total Suspended Solids·L-1) in the reactor sludge. This flux range confirms that fouling is the main issue that can limit the spread of AnMBR potential for the studied stream. No clear correlation was found between CFV or SRT vs. fouling rate, in terms of either TMP·time-1 or permeability·time-1. Operational limitations were observed: irreversible fouling, scaling, ragging and sludging. All the mentioned phenomena could have contributed to the high data dispersion of experimental results.